PENGGUNAAN BAHAN PENYIMPAN AIRDAN VOLUME PEMBERIAN AIR TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensisJacq.)DI MAIN NURSERY - Martha K, Henni; Khoiri, M. Amrul (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to determine the effect of the storage material and the volume of irrigation water on the growth of oil palm seedlings in the Main Nursery and have been implemented in the Technical Implementation Unit of the Faculty of Agriculture, University of Riau from June to October 2014. The study used completely randomized design (CRD) with two factorial factors and three replications. The first factor is the use of water-storage material (A), which consists of 4 levels: A0: Without the use of water-retaining material A1: Hydrogel 25 g / 10 kg soil, A2: Cocopeat 500 g / 10 kg soil, A3: Trunk bananas 50 g / 10 kg of the ground and the second factor is the volume of irrigation (V), which consists of three levels, namely: V1: 1 liter / day / bib it V2: 1.5 liters / day / seed V3: 2 liters / day / seed. The results showed the use of water storage material and the volume of water giving no real effect on seedling height increase, in the number of leaves, wrap accretion hump, dry weight of seed and seedling quality indices but significant effect on the ratio of the root crown. Hydrogel combination of 25 g / 10 kg soil and water provision volume 1 liters / day / seed tends to further increase in the number of leaves, wrap accretion hump seed, seedling dry weight, and seed quality index, while the combination of cocopeat 500 g / 10 kg soil and volume the provision of water 2 liters / day / seed tends to further increase the high accretion canopy ratios of seed and seedling roots. The growth of oil palm seedlings tend to be better with the use of water storage hydrogel material and cocopeat. The growth of oil palm seedlings tend to be better than the entire treatment volume of water provision. Keywords: Palm oil, water-retaining materials, water